2017
DOI: 10.3390/agriculture7030022
|View full text |Cite
|
Sign up to set email alerts
|

Development and Evaluation of Poly Herbal Molluscicidal Extracts for Control of Apple Snail (Pomacea maculata)

Abstract: Golden Apple Snail (GAS) is the most destructive invasive rice pest in Southeast Asia. The cost of synthetic molluscicides, their toxicity to non-target organisms, and their persistence in the environment have propelled the research of plant-derived molluscicides. Most research efforts have focused on individual plant extracts for their molluscicidal potency against GAS and have not been proven to be entirely effective in rice field conditions. Selective combination of synergistically acting molluscicidal comp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
8
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 21 publications
(15 citation statements)
references
References 31 publications
1
8
0
Order By: Relevance
“…a-d). DISCUSSION Several toxicological studies have been carried out to evaluate the molluscicidal activities of chemical pesticides, plant extracts and biocides against harmful land snails (Asran, 2001;Gabr et al, 2006;El-Sherbini et al, 2009;Abdel-Haleem, 2013;EL-Sayed et al, 2013Mwonga et al, 2015Prabhakaran et al, 2017). The present study showed that low concentrations of ethanolic Ginger extract caused low mortality percentages after the first day of exposure while the highest mortalities of M. cartusiana snails occurred at high concentrations of Ginger at the third and fourth weeks.The presence of alkaloids, flavonoids, tannins, saponins, terpenoids and phenolic derivativescaused the molluscicidal potency of Ginger (Sharma et al, 2016).…”
Section: Ultrastructural Abnormalitiesmentioning
confidence: 99%
“…a-d). DISCUSSION Several toxicological studies have been carried out to evaluate the molluscicidal activities of chemical pesticides, plant extracts and biocides against harmful land snails (Asran, 2001;Gabr et al, 2006;El-Sherbini et al, 2009;Abdel-Haleem, 2013;EL-Sayed et al, 2013Mwonga et al, 2015Prabhakaran et al, 2017). The present study showed that low concentrations of ethanolic Ginger extract caused low mortality percentages after the first day of exposure while the highest mortalities of M. cartusiana snails occurred at high concentrations of Ginger at the third and fourth weeks.The presence of alkaloids, flavonoids, tannins, saponins, terpenoids and phenolic derivativescaused the molluscicidal potency of Ginger (Sharma et al, 2016).…”
Section: Ultrastructural Abnormalitiesmentioning
confidence: 99%
“…Previous studies indicated that these compounds were also present in concentrated extracts of other Artemisia spp. [15] and in different solvent extracts of Artemisia dubia [5,16]. The presence of these secondary metabolites as bioactive components that were identified during the qualitative phytochemical tests may be responsible for the molluscicidal activity of wormwood EE.…”
Section: Discussionmentioning
confidence: 99%
“…orientalis, known as wormwood (family Compositae; Pamp., 1930), is considered one of the herbal plants that have potential molluscicidal activity. Species of plants of the genus Artemisia have been used for centuries as moth repellants, general pesticides, and as tea or spray to repel slugs and snails [4,5]. Thus, this study investigated the use of wormwood leaf ethanolic extract as molluscicides, specifically on O. hupensis quadrasi, and determined its potential as a molluscicide.…”
Section: Introductionmentioning
confidence: 99%
“…against various rice and vegetable pests and reported the successful control at 10% composition. Prabhakaran et al, (2017) [32] demonstrated the synergistic molluscicidal effect of crude extracts of Nerium indicum, Nicotiana tabacum, Piper nigrum, and Azadirachta indica and the combinations of extracts in binary and tri-herbal combinations against the invasive rice pest (Pomacea maculate). Arivudainambi et al, (2010) [2] evaluated the bioefficacy of extracts of Cleistanthus collinus, Cleome viscose, Gynandropsis pentaphylla, and Andrographis paniculata in comparison with a commercial formulation of neem and the insecticide Endosulfan under field conditions against amaranth leaf caterpillar (Hymenia recurvalis) and reported that the extracts at 7-day application interval, successfully reduced populations of H. recurvalis in Amaranth.…”
Section: Discussionmentioning
confidence: 99%